2014
DOI: 10.1248/bpb.b13-00930
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Cancer Cell Growth by GRP78 siRNA Lipoplex <i>via</i> Activation of Unfolded Protein Response

Abstract: Proteasome inhibitors are a novel class of molecular-targeted anti-cancer drugs that suppress the degradation of malfolded proteins, trigger endoplasmic reticulum (ER) stress, and activate apoptosis signals. Glucose-regulated protein 78 (GRP78), a major ER chaperone, is one of the most important molecules for transduction of unfolded protein response (UPR) signals. In accordance with past findings that expression of GRP78 is elevated in cancer cells and helps to resist stress-induced apoptosis, GRP78 knockdown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 25 publications
1
9
0
3
Order By: Relevance
“…GRP78, a marker of ER stress, has been reported to be up-regulated in RCC and to be involved in the growth of RENCA renal carcinoma cells [23, 24, 30]. To explore whether the anti-tumor function of miR-30a-5p in ccRCC is mediated by modulating the expression of GRP78, we initially analyzed the GRP78 expression pattern in ccRCC tissues and RCC cell lines.…”
Section: Resultsmentioning
confidence: 99%
“…GRP78, a marker of ER stress, has been reported to be up-regulated in RCC and to be involved in the growth of RENCA renal carcinoma cells [23, 24, 30]. To explore whether the anti-tumor function of miR-30a-5p in ccRCC is mediated by modulating the expression of GRP78, we initially analyzed the GRP78 expression pattern in ccRCC tissues and RCC cell lines.…”
Section: Resultsmentioning
confidence: 99%
“…in ER-stress mediated apoptosis (35). Also, Matsumoto et al reported that overexpression of Bcl-2 blocked CHOP-induced apoptosis (36). On the other hand, we treated A549 cells with the CHOP siRNA under hyperoxia, the results showed the expression of Bcl-2 increased, while the expression of Bax decreased, which further supported our hypothesis on the role of GRP78-CHOP-Bcl-2/Bax pathway in ER related apoptosis of lung epithelial cells under hyperoxia.…”
Section: Discussionmentioning
confidence: 99%
“…ER stress refers to a condition in which normal ER function is impaired, leading to accumulation of unfolded or mis-folded proteins in the ER lumen in myocardial I/R injury. In the case of severe or prolonged ER stress, its responses exceed handling ability of GRP 78 and result in the activation of ER stress related apoptosis signaling pathways [ 24 ]. Caspase 12 is required for apoptosis induced specifically by ER stress.…”
Section: Discussionmentioning
confidence: 99%